The Association Between Plasma Copper Concentration and Prevalence of Diabetes in Chinese Adults With Hypertension - Cui, Zhixin; Chen, Hong; Lu, Wenhai; Wang, Ping; Zhou, Ziyi; Zhang, Nan; Wang, Zhuo; Lin, Tengfei; Song, Yun; Liu, Lishun; Huang, Xiao; Chen, Ping; et al. (Frontiers in Public Health, 2022)
Objective The relationship between plasma copper concentration and prevalence of diabetes in adults with hypertension is unclear. We aimed to determine the association between plasma copper concentration and prevalence of diabetes in Chinese adults with hypertension. Methods A total of 2,579 participants (697 cases and 1,882 controls) was included in this cross-sectional study. Plasma copper concentrations were determined by inductively coupled plasma mass spectrometry. Multivariable logistic regression model was used to determine the association between plasma copper concentration and prevalence of diabetes. Results According to the logistic regression analyses, the adjusted OR for the prevalence of diabetes in participants with plasma copper concentration ≥109.4 μg/dL was 1.26 (1.00, 1.58) compared with those with plasma copper concentration <109.4 μg/dL (P = 0.048). The association was no longer significant following further adjusting for serum high-density lipoprotein cholesterol (HDL-C) concentration as a potential confounder. Stratified analyses demonstrated that serum HDL-C concentration significantly modified the association between plasma copper concentration and prevalence of diabetes (P-interaction = 0.043). In the strata of serum HDL-C concentration ≥1.2 mmol/L, a 56% increased prevalence of diabetes was observed in participants with plasma copper concentration ≥109.4 μg/dL compared with those with plasma copper concentration <109.4 μg/dL (P = 0.008). No significant relationship between plasma copper concentration and prevalence of diabetes was found in other strata. Conclusion Our findings suggested that high plasma copper concentration (≥109.4 μg/dL) was associated with increased prevalence of diabetes in Chinese hypertensive adults with serum HDL-C concentration ≥1.2 mmol/L.